Pharmacokinetics of Dexmedetomidine in Infants and Children After Orthotopic Liver Transplantation. (January 2020) - Damian, Mihaela A.; Hammer, Gregory B.; Elkomy, Mohammed H.; Frymoyer, Adam; Drover, David R.; Su, Felice
Abstract : BACKGROUND: Dexmedetomidine (DEX) is a sedative and analgesic medication that is frequently used postoperatively in children after liver transplantation. Hepatic dysfunction, including alterations in drug clearance, is common immediately after liver transplantation. However, the pharmacokinetics (PK) of DEX in this population is unknown. The objective of this study was to determine the PK profile of DEX in children after liver transplantation. METHODS: This was a single-center, open-label PK study of DEX administered as an intravenous loading dose of 0.5 μg/kg followed by a continuous infusion of 0.5 μg/kg/h. Twenty subjects, 1 month to 18 years of age, who were admitted to the pediatric intensive care unit after liver transplantation were enrolled. Whole blood was collected and analyzed for DEX concentration using a dried blood spot method. Nonlinear mixed-effects modeling was used to characterize the population PK of DEX. RESULTS: DEX PK was best described by a 2-compartment model with first-order elimination. A typical child after liver transplantation with an international normalized ratio (INR) of 1.8 was found to have a whole blood DEX clearance of 52 L/h (95% confidence interval [CI], 31–73 L/h). In addition, intercompartmental clearance was 246 L/h (95% CI, 139–391 L/h), central volume of distribution was 186 L/70 kg (95% CI, 140–301 L/70 kg), and peripheral volume of distribution was 203 L (95% CI, 123–338 L). Interindividual variability ranged from 11% to 111% for all parameters. Clearance was not found to be associated with weight but was found to be inversely proportional to INR. An increase in INR to 3.2 resulted in a 50% decrease in DEX clearance. Weight was linearly correlated with central volume of distribution. All other covariates, including age, ischemic time, total bilirubin, and alanine aminotransferase, were not found to be significant predictors of DEX disposition. CONCLUSIONS: Children who received DEX after liver transplantation have large variability in clearance, which was not found to be associated with weight but is influenced by underlying liver function, as reflected by INR. In this population, titration of DEX dosing to clinical effect may be important because weight-based dosing is poorly associated with blood concentrations. More attention to quality of DEX sedation may be warranted when INR values are changing.